English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

http://geocities.com/jsprplc2006/eq2.jpg

2007-01-15 13:17:24 · 2 answers · asked by jsprplc2006 4 in Science & Mathematics Mathematics

2 answers

Let A = ∫ (0 to π) x f(sin x) dx
= ∫ (π to 0) (π-u) f(sin (π-u)) (-du), subs. u = π-x
= ∫ (0 to π) (π-u) f(sin u) du
= π ∫ (0 to π) f(sin u) du - ∫ (0 to π) u f(sin u) du
= π ∫ (0 to π) f(sin u) du - A
=> 2A = π ∫ (0 to π) f(sin u) du
=> A = (π/2) ∫ (0 to π) f(sin x) dx as required.

2007-01-15 13:29:39 · answer #1 · answered by Scarlet Manuka 7 · 1 0

Let x = pi - u and notice that u = pi-x, du = -dx
and sin(pi-x ) = sin x.
I'll let you carry on from here.

2007-01-15 22:49:33 · answer #2 · answered by steiner1745 7 · 0 0

fedest.com, questions and answers